PEMANFAATAN LIMBAH ORGANIK KULIT PISANG AWAK (Musa balbisiana) SEBAGAI BAHAN SEDIAAN SABUN PADAT UNTUK MENANGKAL RADIKAL BEBAS - Rosa Mardiana; Yuniati Yuniati; Sasmiati Farach Dita (Lantanida Journal, 2022)
Indonesia is one of the largest banana producers. Along with the high productivity of bananas, the amount of banana peel waste also increases. When harvesting bananas, the skin, stems and leaves of bananas (about 80%) are removed without further processing. This is lead to the high amount of banana peel waste, so that there is a need for countermeasures for banana peels to have value. The purpose of this research was to utilize organic waste into a product that have value. The extraction method used in this research was maceration. Banana peel extract (Musa balbisiana) is used to make solid soap preparations by heating, then adding oil and reacting with alkaline solution at a temperature of 50˚C, so that a soap base was obtained. The test conducted on solid soap preparations were organoleptic tests, pH tests, foam stability tests, phytochemical screening, and antioxidant tests. The results showed that the solid soap did not change shape and odor, and had a pH that was in accordance with the standards for skin, namely pH 9-11. The antioxidant test results showed that at a concentration of 10 ppm, banana peel extract had a higher percentage of free radical inhibition than Vitamin C, namely 58.54 and 5366 respectively.